Avian influenza: Situation at present - Cabezas Fernández del Campo, José Antonio (Real Academia Nacional de Farmacia, 2006)
This communication, which follows and amplifies previous papers by the author, published by the Real Academia Nacional de Farmacia, as indicated on its web page (www.ranf.com), is mainly concerned with the following issues: a) The role of the influenza viral glycoprotein named hemagglutinin (HA) in the selective binding and entry of this virus into the host cell; and also how certain modifications in the structure of this glycoprotein influence the pathogenicity of the avian influenza H5N1 subtype virus. b) The mechanisms of avian influenza transmission both by reassortment of genes from several sources and by gene mutation. c) The present danger for birds and humans arising from the infectivity of the H5N1 virus. d) The use of resources and drugs —excluding those related to the inhibition of neuraminidase, NA (since they will be addressed in a forthcoming publication by the author)— to combat the eventual risk of epidemies/ pandemic. La presente comunicación, que es continuación y ampliación de trabajos anteriores del autor sobre virus de la gripe o influenza, publicados por la Real Academia Nacional de Farmacia e indicados en la página web de la misma (www.ranf. com), se refiere principalmente a los siguientes aspectos: a) La importancia de la glicoproteína vírica denominada hemaglutinina (HA) en el proceso de fijación selectiva y penetración de este virus en la célula hospedadora; y cómo ciertas modificaciones de la estructura de dicha glicoproteína afectan a la patogenicidad del virus de la gripe aviar subtipo H5N1. b) Los mecanismos de transmisión de la influenza aviar por reagrupamiento («reassortment») de genes de varias procedencias, o por mutación de genes. c) La peligrosidad actual en aves y en seres humanos a causa de dicho virus H5N1. d) Algunos de los posibles remedios y fármacos —excluidos los inhibidores de las neuraminidasa, NA (por ser objeto de otra próxima publicación del autor)— para combatir el riesgo de eventuales epidemias/pandemia.